Rating Migrations: The Effect of History and Time. (June 2014) - Dang, Huong; Partington, Graham
<x xml:space="preserve">Abstract</x> We examine the effect of rating history and the passage of time on the rating migration hazard for corporate debt issuers. Controlling for industry effects and the evolution of business and political cycles, the results consistently show that the next change of rating depends more strongly on rating history than it does on the current rating. However, there are significant interactions between the main effects of rating history and the duration of the current rating. The result is substantial decay in the effects of rating history the longer a rating remains unchanged. This decay effect is stronger for downgrades and for ratings in the speculative category.